SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170730-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Asphaltene Transport over Geologic Time Aids in Explaining the Distribution of Heavy Oils and Solid Hydrocarbons in Reservoirs

Abstract: Asphaltenes are a very important component of reservoir fluids. They have a huge impact on crude oil viscosity and are a Flow Assurance concern. They can undergo a phase transition, giving rise to tar mats that seal aquifers precluding aquifer sweep. Local tar deposits can act as a drilling hazard. Upstructure tar (or bitumen) deposition can occur which can flow with produced light hydrocarbons greatly reducing the productivity index. In EOR, miscible gas injection can also give rise to asphaltene deposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The asphaltenes in the heavy oil column above are equilibrated and excellently match the Yen-Mullins model. [52] The numerical schematics in Fig. 5 is consistent with the compositional distribution of this reservoir.…”
Section: Numerical Simulations and Case Studiessupporting
confidence: 72%
See 1 more Smart Citation
“…The asphaltenes in the heavy oil column above are equilibrated and excellently match the Yen-Mullins model. [52] The numerical schematics in Fig. 5 is consistent with the compositional distribution of this reservoir.…”
Section: Numerical Simulations and Case Studiessupporting
confidence: 72%
“…Clusters observed in oilfield studies have generally been close to 5.0 nm [3,44]. The FHZ EoS is increasingly utilized in oilfield studies [52]. Other formalisms, such as SAFT (statistical associating fluid theory) modeling, have also been used to describe asphaltene gradients in oilfields [53].…”
Section: Introductionmentioning
confidence: 99%
“…3 The adsorption and/or deposition of asphaltenes onto formation grains is one of the primary causes of formation damage in oil reservoirs, which has been one of the major unresolved flow assurance problems in the oil industry. [4][5][6][7] Asphaltenes, which are the heaviest and most polar compounds in crude oil, are typically defined as the solubility class obtained from crude oil by fractionation using solvents.…”
Section: Introductionmentioning
confidence: 99%
“…21 studied the adsorption of n-C 7 asphaltenes from mineral oil on to several hydrophilic clays minerals. 3 The authors found that the adsorption is mainly due to the interactions of the polar parts of the asphaltenes with the polar parts of the surface resulting in a hydrophobic shell of asphaltenes and allowing the adsorption of a second layer of asphaltenes that is more hydrophilic for the buildup of outward-facing polar functional groups. 19,21 Several studies 21,[35][36][37] have shown that kaolinite and calcite are very active minerals for asphaltene adsorption and that kaolinite have the highest adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Some Pliocene reservoirs are still actively charging and have not had sufficient time to equilibrate or even to complete their charge. [5] In these cases, thermodynamic equilibration of the fluids is simply precluded and fluid properties variation, such as gas-oil ratio (GOR) and saturation pressure in low GOR fluids, and the asphaltene onset pressure [6] can occur. Consequently, the corresponding fluid gradient is often not equilibrated.…”
Section: Introductionmentioning
confidence: 99%